The role of calcium and CaMKII in sleep - Wang, Yuyang; Minami, Yoichi; Ode, Koji L.; Ueda, Hiroki R. (Frontiers in Systems Neuroscience, 2022)
Sleep is an evolutionarily conserved phenotype shared by most of the animals on the planet. Prolonged wakefulness will result in increased sleep need or sleep pressure. However, its mechanisms remain elusive. Recent findings indicate that Ca2+ signaling, known to control diverse physiological functions, also regulates sleep. This review intends to summarize research advances in Ca2+ and Ca2+/calmodulin-dependent protein kinase II (CaMKII) in sleep regulation. Significant changes in sleep phenotype have been observed through calcium-related channels, receptors, and pumps. Mathematical modeling for neuronal firing patterns during NREM sleep suggests that these molecules compose a Ca2+-dependent hyperpolarization mechanism. The intracellular Ca2+ may then trigger sleep induction and maintenance through the activation of CaMKII, one of the sleep-promoting kinases. CaMKII and its multisite phosphorylation status may provide a link between transient calcium dynamics typically observed in neurons and sleep-wake dynamics observed on the long-time scale.